Model studies on the dimerization of 1,3-diacetylenes - Haberhauer, Gebhard; Gleiter, Rolf; Fabig, Sven (The journal of organic chemistry, 2015)
By means of high-level quantum chemical calculations (B2PLYPD and CCSD(T)), the dimerization of 1,3-diacetylenes was studied and compared to the dimerization of acetylene. We found that substituted 1,3-diacetylenes are more reactive than the corresponding substituted acetylenes having an isolated triple bond. The most reactive centers for a dimerization are always the terminal carbon atoms. The introduction of a test reaction allows the calculation of the relative reactivity of individual carbon centers in phenylacetylene, phenylbutadiyne, and phenylhexatriyne. A comparison shows that the reactivity of the terminal carbon atoms increases with increasing numbers of alkyne units, whereas the reactivity of the internal carbon atoms remains very low independent of the number of alkyne units.
Gesehen am 22.02.2021